Musik Iringan Tari Pencak Silat Rancak Takasima dalam Koreografi Idiom Baru - Rustiyanti, Sri; Listiani, Wanda; Ningdyah, Anrilia E.M.; Dwiatmini, Sriati; Suryanti, Suryanti (Institut Seni Indonesia Yogyakarta, 2024)
The objective of this article is to elucidate the significance of music in complementing the choreography of the innovative Pencak Silat dance form known as Rancak Takasima. In the realm of dance performance, music plays a pivotal role as an accompaniment. While dance accompaniment music can exist independently, the reciprocal is not true – dance cannot be fully actualized without the support of accompanying music. Essentially, dance and music are inseparable counterparts, mutually enhancing and interdependent, akin to the interconnected sides of a coin. In the crafting of a dance performance, the presence of dance accompaniment, specifically in the form of musical compositions, serves as a crucial catalyst. This concept is referred to as external music, encompassing instruments like percussion, strings, and wind instruments employed as accompaniment in dance. In contrast, internal music entails sounds not generated by instrumental music but rather emanating from the dancer or performer, such as vocals, rhythmic footwork, finger snaps, chest and thigh percussion, hand claps, elbow taps, and the use of galembong (a patting technique on wide-legged pants). This research used a qualitative method with a dance ethnographic approach model. This technique research collected data through diverse methods such as observation, demonstration, interviews, and documentation during creating the creative process of choreographing the new idiom of Rancak Takasima. The development of dance accompaniment music and choreography unfolds gradually, originating from initially abstract ideas and taking visual form through Seni Pencak movements and the musicality crafted by the internal body's dancers themselves and using sound of 'serut bambu' props. The research outcomes showcase the Seni Pencak dance accompaniment music model as a valuable contribution to the evolution of Pencak Silat Nusantara dance. This particular dance accompaniment music model integrates seamlessly into the new idiom's choreography, featuring the distinctive ‘serut bambu’ property that generates the accompanying dance music. This research result conducted under Penelitian Terapan Jalur Hilirisasi (PTJH) scheme. For those interested in learning more, the dance accompaniment music and Seni Pencak choreography of Rancak Takasima can be easily accessed through the website https://www.dayaversapasua.tech.